Analysis of the Diurnal Changes in the Water-Soluble Ion Concentration in Wuhan between 2016 and 2019 - Yingying Sun (Atmosphere, 2022)
This study uses online monitoring data from the Hubei Environmental Monitoring Center’s Atmospheric Compound Pollution Automatic Monitoring Station from 2016 to 2019 to analyze the diurnal changes in the concentration of water-soluble ions in particulate matter in Wuhan. During the study period, the concentrations of SO2, NO3−, and SO42− changed significantly, while those of NH4+, NH3, and Ca2+ exhibited minimal differences. SO2 and NO3− showed an annually increasing trend, while NH4+ and SO42− exhibited an annually decreasing trend. The ion concentration was generally higher in the winter and spring and lower in the summer and autumn. The concentration of water-soluble ions was generally higher during the day than at night. However, the “weekend effect” on the change in ion concentrations was substantial and higher during the day than at night. This effect was the strongest for NO3− and the weakest for NH3. These changes in the weekend effect of water-soluble ions in particulate matter clearly revealed the impact of periodic human activities on atmospheric pollution. Taken together, the results of this novel study reveal the diurnal pollution characteristics and “weekend effect” of water-soluble ions with high concentrations in atmospheric aerosols in Wuhan over a four-year period, thus providing relevant insights for Wuhan’s atmospheric mitigation plan.